2022
DOI: 10.54530/jcmc.708
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome in Pregnancy Beyond the Expected Date of Delivery in a Tertiary Care Hospital of Nepal

Abstract: Background: The risk to the mother and the fetus increase with advancing gestation age. Our study aims to study the maternal and fetal outcome in pregnancy extending beyond the expected date of delivery so that safe timings of induction and appropriate mode of delivery can be determined. Methods: We conducted a retrospective study of 152 patients with pregnancy beyond the expected date who presented to the department of Obstetrics and Gynecology, College of Medical Sciences Teaching Hospital from the time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…Nulliparity is a recognized risk factor for postdate pregnancy [1] and various studies have reported incidence of 55.7% [10] , 63% [26] , and 74% [28] among primigravida. In contrast, this study found a higher prevalence among multiparous women, similar to reports of 53.29% and 54% by Chhetri et al [31] and Naz et al [34] . The higher occurrence among nulliparous women has been suggested to be likely due to inaccuracies in recollecting the exact date of last normal menstrual period, especially when the pregnancy is unplanned [10] and particularly where pregnancy dating was done by last menstrual period alone [35] .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Nulliparity is a recognized risk factor for postdate pregnancy [1] and various studies have reported incidence of 55.7% [10] , 63% [26] , and 74% [28] among primigravida. In contrast, this study found a higher prevalence among multiparous women, similar to reports of 53.29% and 54% by Chhetri et al [31] and Naz et al [34] . The higher occurrence among nulliparous women has been suggested to be likely due to inaccuracies in recollecting the exact date of last normal menstrual period, especially when the pregnancy is unplanned [10] and particularly where pregnancy dating was done by last menstrual period alone [35] .…”
Section: Discussionsupporting
confidence: 90%
“…There was a decreased rate of spontaneous vaginal delivery and increased rate of CD as the gestational age advanced. This finding has been corroborated by studies by Chhetri et al [31] , Bhriegu et al [38] , and Reddy [39] . While the study by Chhetri et al [31] reported the highest proportion of CD (64.28%) in women between 41-42 weeks, we found a proportion of 49.4% at 41 weeks, rising to 77.8% in those ≥42 weeks.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations